Comparative genomic analysis of Ralstonia solanacearum reveals candidate avirulence effectors in HA4-1 triggering wild potato immunity - Huang, Mengshu; Tan, Xiaodan; Song, Botao; Wang, Yuqi; Cheng, Dong; Wang, Bingsen; Chen, Huilan (Frontiers in Plant Science, 2023)
Ralstonia solanacearum is the causal agent of potato bacterial wilt, a major potato bacterial disease. Among the pathogenicity determinants, the Type III Secretion System Effectors (T3Es) play a vital role in the interaction. Investigating the avirulent T3Es recognized by host resistance proteins is an effective method to uncover the resistance mechanism of potato against R. solanacearum. Two closely related R. solanacearum strains HA4-1 and HZAU091 were found to be avirulent and highly virulent to the wild potato Solanum albicans 28-1, respectively. The complete genome of HZAU091 was sequenced in this study. HZAU091 and HA4-1 shared over 99.9% nucleotide identity with each other. Comparing genomics of closely related strains provides deeper insights into the interaction between hosts and pathogens, especially the mechanism of virulence. The comparison of type III effector repertoires between HA4-1 and HZAU091 uncovered seven distinct effectors. Two predicted effectors RipA5 and the novel effector RipBS in HA4-1 could significantly reduce the virulence of HZAU091 when they were transformed into HZAU091. Furthermore, the pathogenicity assays of mutated strains HA4-1 ΔRipS6, HA4-1 ΔRipO1, HA4-1 ΔRipBS, and HA4-1 ΔHyp6 uncovered that the absence of these T3Es enhanced the HA4-1 virulence to wild potato S. albicans 28-1. This result indicated that these T3Es may be recognized by S. albicans 28-1 as avirulence proteins to trigger the resistance. In summary, this study provides a foundation to unravel the R. solanacearum-potato interaction and facilitates the development of resistance potato against bacterial wilt.